MAPPING OF LANDSLIDE-PRONE AREAS ON ENDE-WOLOWARU ROAD SECTION ENDE REGENCY BASED ON GEOGRAPHIC INFORMATION SYSTEM - Maria Sonya Kae; Arfita Rahmawati; Bella Theo Tomi Pamungkas (Universitas Sebelas Maret (UNS), 2024)
Landslides on the Ende - Wolowaru road, Ende Regency often occur every year, especially in the rainy season. Therefore, research was carried out to determine the level of vulnerability to landslides on the Ende - Wolowaru road section, Ende Regency, using an estimation model referring to Puslittanak research in 2004. Mapping of landslide-prone areas was carried out at a radius of 250 meters along the Ende - Wolowaru road section, Ende Regency with area 2,514 ha. The analysis used GIS analysis, such as: scoring and overlay methods based on 2004 Puslittanak Department of Agriculture estimation model. The parameters used are rainfall, rock type, slope, land cover and soil type. The results of the analysis in this study show that the level of vulnerability to landslides at the research location consists of a non-prone class covering an area of 13.38 ha, a vulnerable class covering an area of 1,620.38 ha and a very vulnerable class covering an area of 880.65 ha and (2) the level of validation mapping results that is equal to 88%.